Effect of Intake Valve Gap Adjustment Variation on Fuel Consumption in Daewoo 4dwy-30 Diesel Motorcycle - Eko Julianto; Fuazen; Prayoga, Yongki; Iwan, Muhammad; Gunarto; Sarwono, Eko; Yunus Nasution, Ahmad (DINAMIS, 2024)
The valve mechanism system on a 4 stroke diesel motor functions as an opening or closing mechanism which is used as a way for air to enter the combustion chamber or as an outlet for residual combustion gases from the combustion chamber. To maximize diesel engine performance, valve clearance adjustments need to be carried out periodically. This research aims to determine the effect of variations in intake valve gap adjustment on fuel consumption on the Daewoo 4 DWY-30 diesel motorbike. This research uses experimental methods and is quantitative research, namely presenting the results of experiments in the laboratory on test objects. The research results show that there is an influence of variations in intake valve gap adjustment on fuel consumption. The highest fuel consumption is at the intake valve gap setting of 0.20 mm, and the lowest fuel consumption is at the intake valve gap setting of 0.60 mm.